A Rodent Model of Exposure Therapy: The Use of Fear Extinction as a Therapeutic Intervention for PTSD - Paredes, Denisse; Morilak, David A. (Frontiers in Behavioral Neuroscience, 2019)
The symptoms of post-traumatic stress disorder (PTSD) include cognitive impairment related to medial prefrontal cortical dysfunction. Indeed, a deficit of cognitive flexibility, i.e., an inability to modify previously learned thoughts and behaviors based on changes in the environment, may underlie many of the other symptoms of PTSD, such as changes in mood, hyper-arousal, intrusive thoughts, exaggerated and over-generalized fear, and avoidance behavior. Cognitive-behavioral therapies target the cognitive dysfunction observed in PTSD patients, training them to recalibrate stress-related perceptions, interpretations and responses. Preclinically, the extinction of conditioned fear bears resemblance to one form of cognitive therapy, exposure therapy, whereby an individual learns, through repeated exposure to a fear-provoking stimulus in a safe environment, that the stimulus no longer signals imminent threat, and their fear response is suppressed. In this review, we highlight recent findings from our lab using fear extinction as a preclinical model of exposure therapy in rodents exposed to Chronic Unpredictable Stress. We specifically focus on the therapeutic effects of extinction on stress-compromised set-shifting as a measure of cognitive flexibility, and active vs. passive coping behavior as a measure of avoidance. Finally, we discuss mechanisms involving activity and plasticity in the medial prefrontal cortex necessary for the therapeutic effects of extinction on cognitive flexibility and active coping.